STRATEGIES, METHODS, AND OPTIMAL SOLUTIONS FOR IMPROVING TEACHERS' ORGANIZATIONAL COMMITMENT - Astuti, Siwi Puji; Setyaningsih, Sri; Wulandari, Dian (Yayasan Education and Social Center, 2025)
commitment. The method used in this study is quantitative, with 160 public junior high school teachers as respondents. Data analysis techniques use SEM-PLS, where variable analysis is performed using path analysis to find strategies. Meanwhile, to find methods and optimal solutions, indicator analysis is performed using SITOREM. The results of the study show that the right strategy can increase teachers' organizational commitment by looking at the path analysis values, starting from the largest, namely: psychological empowerment, authentic leadership, pedagogical competence, and interpersonal communication. The optimal solutions, considering the order of the indicators to be improved, are: 1) competence, 2) meaning, 3) impact, 4) sensitivity, 5) consistency, 6) transparency, 7) learning design, 8) learning evaluation, 9) learning implementation, 10) self-understanding, 11) empathy, 12) adaptability, 13) sincerity, 14) pride, and 15) hope.